2009
DOI: 10.1002/aic.11966
|View full text |Cite
|
Sign up to set email alerts
|

Transferable intermolecular potentials for carboxylic acids and their phase behavior

Abstract: in Wiley InterScience (www.interscience.wiley.com).Transferable step potentials are characterized for 39 carboxylic acids. The reference potential is treated with discontinuous molecular dynamics, including detailed molecular structure. Thermodynamic perturbation theory is used to interpret the simulation results and to provide an efficient basis for molecular modeling and characterization of the attractive forces. Four steps are used for representation of the attractive forces with only the first and last ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 118 publications
2
16
0
Order By: Relevance
“…Here it is worth mentioning that such low molecular weight acids present a large deviation form ideal gas behavior (Z significantly deviates from unity) due to strong dimerization even at low pressures and even below 1 atm. 3 It is worth mentioning that the heat of vaporization and the compressibility factors are not satisfactorily described if the formation of dimers is not accounted for, in accordance with previous literature studies. 3,29 This is clearly shown in Figure 5, where the NRHB calculations are compared with the literature data for two cases: modeling acetic acid assuming a hydrogen bonding behavior similar to that of alcohols (one proton donor and one proton acceptor on every molecule that are able to cross associate and form oligomers), which is a frequently used approach 25 , and restricting the formation of hydrogen bonds to the formation of cyclic dimers.…”
Section: Fluidsupporting
confidence: 70%
See 3 more Smart Citations
“…Here it is worth mentioning that such low molecular weight acids present a large deviation form ideal gas behavior (Z significantly deviates from unity) due to strong dimerization even at low pressures and even below 1 atm. 3 It is worth mentioning that the heat of vaporization and the compressibility factors are not satisfactorily described if the formation of dimers is not accounted for, in accordance with previous literature studies. 3,29 This is clearly shown in Figure 5, where the NRHB calculations are compared with the literature data for two cases: modeling acetic acid assuming a hydrogen bonding behavior similar to that of alcohols (one proton donor and one proton acceptor on every molecule that are able to cross associate and form oligomers), which is a frequently used approach 25 , and restricting the formation of hydrogen bonds to the formation of cyclic dimers.…”
Section: Fluidsupporting
confidence: 70%
“…For this reason, the use of experimental data for other properties, such as enthalpies of vaporization and vapor phase compressibility factors has been suggested. 3,24,29 However, for all hydrogen bonding fluids, such difficulty mainly arises from the fact that the parameters that characterize the strength of the various intermolecular interactions (physical or hydrogen bonding), are highly correlated to each other. 38,39 Consequently, the estimation of the association (dimerization) parameters (E dm and S dm ) for carboxylic acids is probably the most important step towards the parametrization of such fluids.…”
Section: Pure Fluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Alder et al [26] reported MD simulations for systems of hard spheres using an event-driven algorithm in 1957, 7 years before Rahman's soft potential simulations. Since then, many discrete potential force fields have been developed for a wide range of systems, including granular materials, [27] simple molecular systems (e.g., SPEADMD [28] ) such as mixtures of hydrocarbons, [28] ethers, [28] alcohols, [29] amines, [29] and carboxylic acids, [30] block copolymer micelles [31] and organized mesophases, [32] and detailed models (e.g., PRIME [33] ) for polypeptide [34,35] and protein [36] solutions.These models not only offer qualitative insight to these systems but also provide quantitative predictions for such properties as vapor-liquid phase equilibrium. [28] In addition, the models are detailed enough to realistically capture protein structure, but sufficiently efficient to examine folding and aggregation.…”
Section: N Bannerman R Sargant and L Luementioning
confidence: 99%